2003
DOI: 10.1164/rccm.200201-057oc
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Nitric Oxide Modifies Left Ventricular Diastolic Stress in the Presence of Vasoactive Agents in Heart Failure

Abstract: Nitric oxide (NO) inhalation therapy has been widely used in several diseases with pulmonary hypertension. However, application of NO inhalation therapy remains controversial in heart failure. Cardiovascular effects of inhaled NO (iNO) were evaluated in dogs before and after induction of heart failure with and without infusion of vasoactive agents. iNO did not affect the baseline left ventricular (LV) function or the response to isoproterenol in control conditions or heart failure induced by procainamide. Pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Importantly, the positive inotropic response to ␤-adrenergic stimulation is known to be suppressed by NO (18,42,43). We have previously demonstrated that LV dysfunction is indirectly aggravated even with inhaled NO in heart failure (32).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the positive inotropic response to ␤-adrenergic stimulation is known to be suppressed by NO (18,42,43). We have previously demonstrated that LV dysfunction is indirectly aggravated even with inhaled NO in heart failure (32).…”
Section: Discussionmentioning
confidence: 99%
“…This seeming disregard for the use of inhaled vasodilators in the large patient population with CHF is primarily based on the results of earlier clinical trials with systemic vasodilators, such as nifedipine, oral milrinone, flosequinan, or epoprostenol (Flolan), which failed to show therapeutic benefit and frequently even worsened clinical outcome (10 -12, 21). Adverse systemic or pulmonary effects including hypotension with reduced coronary perfusion (22), left ventricular volume overload (14), or pulmonary edema formation by opening of precapillary sphincters in the lung (13) may have contributed to these detrimental results. Albeit the cause for these therapeutic failures remains incompletely understood, the studies identify systemic afterload reduction as a delusive strategy for the treatment of patients with CHF.…”
Section: Discussionmentioning
confidence: 99%
“…Because systemic administration of vasodilators in CHF yielded detrimental results in several clinical trials (10 -12), we further speculated that inhalative delivery may be superior due to its relative selectivity for the pulmonary vasculature. A major concern for the use of inhaled vasodilators in CHF are potential side effects, which include edema formation due to the opening of precapillary sphincters (13) or left ventricular volume overload (14). Hence, systematic studies on the putative benefits and adverse effects of inhaled vasodilators in pulmonary hypertension with left heart disease are required.…”
mentioning
confidence: 99%
“…LV pressure, the rate of LV pressure change (LV dP/dt), and the time constant of LV isovolumic relaxation () were measured by a catheter-tipped transducer (PC-350; Millar, Houston, TX) inserted from the right carotid artery into the LV. A 5-MHz single-plane transducer for transesophageal echocardiography (SSD-830; Aloka, Tokyo, Japan) was placed just behind the LV to monitor changes in LV dimensions (29).…”
Section: Experimental Animals and Preparationmentioning
confidence: 99%